Estimación de biomasa y carbono almacenado en un fragmento de bosque húmedo tropical, CIEFOR, Puerto Almendra, Rio Nanay, Iquitos – 2023 - Panaifo Iruyari, Rosa Antonia (Universidad Nacional de la Amazonía Peruana, 2025)
The study was carried out in a forest fragment with low terrace characteristics, a flood-prone area, of CIEFOR-Puerto Almendra. The overall objective was to estimatethe aboveground biomass and stored carbon in a tropical rainforest fragment, using two allometries or mathematical models, by diameter class and by tree species and in turn determine which allometric equation is appropriate from Álvarez (2012) cited by Casas (2013, p. 12); by Chave et al., (2014, p. 6). In this sense it is shown that biomass and stored carbon increase with the diameter increase of the trees, in the diameter class of 50 cm the highest values of biomass and stored carbon were reported for the Álvarez equationset al., (33656. 15 kg/ha, 16.83 t/ha) and Chavetet al., (45976.74 kg/ha, 22.99 t/ha). The speciesNealchornea yapurensis and Pourouma acuminataThey were identified as the species with the greatest biomass and stored carbon with the Alvarez equationset al., (27031.14 kg/ha, 23618.63 kg/ha; 13.52 t/ha, 11.81 t/ha) and Chavetet al., (40179.48 kg/ha, 27053.42 kg/ha; 20.09 t/ha, 13.53 t/ha). Chave's estimateset al. were consistently higher across all diameter classes, with a total biomass difference of 83,623.38 kg/ha (42.07% higher) and carbon difference of 41.81 t/ha. These differences were statistically significant (Wilcoxon test, p < 0.0001), although both equations showed a high correlation (r = 0.99, p < 0.0001).

El estudio se realizó en un fragmento del bosque con características de terraza baja, zona inundable, del CIEFOR-Puerto almendra. Con el objetivo general de es2aaaaaaaaatimar la biomasa aérea y carbono almacenado en un fragmento de bosque húmedo tropical, utilizando dos alometrías o modelos matemáticos, por clase diamétrica y por especie arbórea y a su vez determinar que ecuación alométrica es la adecuada de Álvarez (2012) citado por Casas (2013, p. 12); por Chave et al., (2014, p. 6). En ese sentido se muestra que la biomasa y el carbono almacenado aumentan con el incremento diamétrico de los árboles, en la clase diamétrica de 50 cm se reportó los mayores valores de biomasa y carbono almacenado para las ecuaciones de Álvarez et al., (33656. 15 kg/ha, 16.83 t/ha) y Chave et al., (45976.74 kg/ha, 22.99 t/ha). Las especies Nealchornea yapurensis y Pourouma acuminata fueron identificadas como las especies con mayor biomasa y carbono almacenado con las ecuaciones de Álvarez et al., (27031.14 kg/ha, 23618.63 kg/ha; 13.52 t/ha, 11.81t/ha) y Chave et al., (40179.48 kg/ha, 27053.42 kg/ha; 20.09 t/ha, 13.53 t/ha). Las estimaciones de Chave et al. fueron consistentemente más altas en todas las clases diamétricas, con una diferencia total de biomasa de 83623.38 kg/ha (42.07% mayor) y de carbono de 41.81 t/ha. Estas diferencias fueron estadísticamente significativas (prueba de Wilcoxon, p < 0.0001), aunque ambas ecuaciones mostraron una alta correlación (r = 0.99, p < 0.0001).
Keywords: Biomasa; Secuestro de carbono; Bosque tropical húmedo; https://purl.org/pe-repo/ocde/ford#4.01.02